Personality Differences of Brain Networks in Placebo Analgesia and Nocebo Hyperalgesia: A Psychophysiological Interaction (PPI) Approach in fMRI. (19th October 2020) - Shi, Yu; Huang, Shimin; Zhan, Hongrui; Wang, Yaping; Zeng, Yanyan; Cai, Guiyuan; Yang, Jianming; Wu, Wen
Abstract : It is generally believed that the placebo response can elicit an analgesic effect, whilst the nocebo response can elicit a hyperalgesia effect in pain. Placebo analgesia and nocebo hyperalgesia effects are increasing concerns for researchers. Growing evidence suggests personality differences have an impact on both placebo and nocebo effects. However, previous studies have not reached a unified conclusion. We designed this study to explore the personality differences of functional magnetic resonance imaging (fMRI) signals in placebo response and nocebo response by using psychophysiological interaction (PPI) analysis. 30 healthy subjects underwent conditioning induction training to establish expectations of placebo effect and nocebo effect, and then, all subjects completed the following experimental procedures: (1) baseline scanning, (2) acute pain model establishment, (3) pain status scanning, and (4) pseudorandom scanning of block design of placebo response or nocebo response. Behavioral data were collected after each scan. The results of this study showed that (1) there were significant differences of VAS placebo intervention between the extrovert group and the introvert group (p = 0.004 ); (2) there were significant differences of VAS nocebo intervention between the extrovert group and the introvert group (p = 0.011 ); (3) there were significant differences between the VAS placebo intervention and VAS pain status (baseline) in both the extrovert group (p < 0.001 ) and the introvert group (p = 0.001 ); (4) there were significant differences between the VAS nocebo intervention and VAS pain status (baseline) in both the extrovert group (p = 0.008 ) and the introvert group (p < 0.001 ). Moreover, there were significant differences in the brain network for placebo and nocebo responses between different personalities. We found that (1) deactivation differences of the pain-related network and limbic system play an important role in personality differences associated with placebo analgesia and (2) differences of control of anxiety and activation of dorsolateral prefrontal cortex may cause the personality differences observed in nocebo hyperalgesia.